Movimientos diversos. Sistematización de la práctica pedagógica en el Centro Crecer Bosa con población en condición de discapacidad. (2022)
This work contains the systematization of professional practice I and II of the Bachelor of Performing Arts of the Antonio Nariño University, which was carried out with a population with disabilities from Centro Crecer Bosa and which was developed from traditional folk dance of the Caribbean specifically cumbia and carnival, seeking to strengthen learning processes in the population with disabilities, dance is implemented as a pedagogical strategy to strengthen the context of the members of Centro Crecer, based on aspects such as their social, cognitive, motor and space environment. temporary